Pentingnya Public Speaking guna Meningkatkan Kompetensi Komunikasi Mahasiswa - Rahmayanti, Stevfani; Asbari, Masduki; Fajrin, Siti Fadilah (Journal of Information Systems and Management (JISMA), 2024)
This research aims to analyze the potential and conditions of learning, analyze improving public speaking skills effectively, increasing the efficiency of learning public speaking, and increasing the attractiveness of learning public speaking. Public speaking skills are still not fully possessed by students. This reluctance to appear in public is due to low self-confidence and lack of mastery of public speaking techniques. This inability causes communication that should be effective to become degraded. In fact, communication misunderstandings often occur in public. This misunderstanding was documented and spread online. Students also become vulnerable to acts of bullying in cyberspace. Public speaking is delivered in the form of storytelling so that it is lighter and easier for students to accept. Apart from being a form of service and concern for the surrounding community, this activity is also a form of implementing the lecturers' knowledge and insights in lectures. This activity shows public speaking skills starting with simple things in the form of storytelling. Public speaking development has 4 techniques that must be mastered. Research is carried out using a development approach. The subjects of action in this research were UNIPI (Indonesian Human Development University) students.